TRANSITIVITY IN BBC NEWS INDONESIA "MAY 1998 RIOTS" NEWS DISCOURSE - Devi Alvionita Alindra (ELT (English Language Teaching Prima Journal), 2023)
This article discusses transitivity in three news discourse texts from the BBC News Indonesia online news website titled "May 1998 Riots." Transitivity is analyzed using a qualitative approach focusing on the types of processes and circumstances present in the texts. Material processes, indicating physical activities, dominate in all texts, and location circumstances are the most frequently occurring. Despite variations in the types of processes and circumstances, their distribution is uneven across the three news discourse texts, indicating diversity in the use of linguistic elements in the news context. In these news texts, material processes have the highest percentage of occurrence, approximately 41.74%, emphasizing the emphasis on physical activities in presenting information. Location circumstances have the highest percentage of occurrence, around 42.07%, highlighting a strong focus on the event's location. Transitivity analysis provides a deeper understanding of information structure in news texts, with material processes and location circumstances being the main focus. This research offers additional insights into the use of transitivities in news discourse texts, emphasizing the dominant role of material processes and location circumstances in conveying information to readers. The diversity in the use of linguistic elements illustrates the complexity and dynamics of news text composition.